2020
DOI: 10.3389/fimmu.2019.03136
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Controlling Foxp3 Expression in Health and Autoimmunity: From Epigenetic to Post-translational Regulation

Abstract: The discovery of the transcription factor Forkhead box-p3 (Foxp3) has shed fundamental insights into the understanding of the molecular determinants leading to generation and maintenance of T regulatory (Treg) cells, a cell population with a key immunoregulatory role. Work over the past few years has shown that fine-tuned transcriptional and epigenetic events are required to ensure stable expression of Foxp3 in Treg cells. The equilibrium between phenotypic plasticity and stability of Treg cells is controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 256 publications
(271 reference statements)
1
63
0
3
Order By: Relevance
“…Subsequently, many studies on the role of miRNAs in Treg differentiation and stability were conducted, mostly using murine models. These studies revealed a more complex picture, with a least 20 miRNAs exerting important effects on Treg development, control of FOXP3 stability and translation, and suppression of Treg function, such as miRNA-155, regulated by FOXP3 and involved in Treg proliferation, and miR-428, a hominidspecific miRNA, that potently and specifically up-regulate FOXP3 expression accelerating the differentiation of human naïve cells to induced Tregs (30)(31)(32). Additionally, it should be recalled that FOXP3 interacts with several RNA-binding proteins, thus playing a role in the posttranscriptional mechanisms involved in RNA stability (33).…”
Section: Foxp3 and Ipexmentioning
confidence: 99%
“…Subsequently, many studies on the role of miRNAs in Treg differentiation and stability were conducted, mostly using murine models. These studies revealed a more complex picture, with a least 20 miRNAs exerting important effects on Treg development, control of FOXP3 stability and translation, and suppression of Treg function, such as miRNA-155, regulated by FOXP3 and involved in Treg proliferation, and miR-428, a hominidspecific miRNA, that potently and specifically up-regulate FOXP3 expression accelerating the differentiation of human naïve cells to induced Tregs (30)(31)(32). Additionally, it should be recalled that FOXP3 interacts with several RNA-binding proteins, thus playing a role in the posttranscriptional mechanisms involved in RNA stability (33).…”
Section: Foxp3 and Ipexmentioning
confidence: 99%
“…Foxp3 transcription is induced in Tregs by T cell receptor (TCR) signaling. Upon its expression, an autoregulatory transcriptional circuit stabilizes Foxp3 gene expression to consolidate Treg differentiation and activate the suppressive function [ 36 ]. The block of Foxp3 elicits Treg depletion and it promotes enhanced stimulation of effector immune mechanisms [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 is a transcription factor that regulates the function of CD4 Treg cells. The molecular mechanisms regulating FOXP3 are complex and consist of finely tuned transcriptional and epigenetic events [ 56 ]. Although the role of BRD4 and inhibition of FOXP3 were previously unknown, our data suggest that BRDs can regulate the expression of FOXP3.…”
Section: Discussionmentioning
confidence: 99%